2006
DOI: 10.1073/pnas.0606312103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular switch for alternative conformations of the HIV-1 V3 region: Implications for phenotype conversion

Abstract: HIV-1 coreceptor usage plays a critical role in virus tropism and pathogenesis. A switch from CCR5-to CXCR4-using viruses occurs during the course of HIV-1 infection and correlates with subsequent disease progression. A single mutation at position 322 within the V3 loop of the HIV-1 envelope glycoprotein gp120, from a negatively to a positively charged residue, was found to be sufficient to switch an R5 virus to an X4 virus. In this study, the NMR structure of the V3 region of an R5 strain, HIV-1JR-FL, in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 21 publications
1
92
0
3
Order By: Relevance
“…V3 mutations 4 and 7 have been implicated in affecting coreceptor usage in functional studies (de Jong et al 1992;Fouchier et al 1992;Hung et al 1999; and structural modeling studies (Cardozo et al 2007;Gorry et al 2007;Rosen et al 2006). These mutations had significant pairwise and higher-order interactions with mutations 1 and 3, as well as other mutations.…”
Section: Discussionmentioning
confidence: 99%
“…V3 mutations 4 and 7 have been implicated in affecting coreceptor usage in functional studies (de Jong et al 1992;Fouchier et al 1992;Hung et al 1999; and structural modeling studies (Cardozo et al 2007;Gorry et al 2007;Rosen et al 2006). These mutations had significant pairwise and higher-order interactions with mutations 1 and 3, as well as other mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Two patterns of resistance mutations defined by early acquisition of either the E560K mutation in HR1 (pathway I) or E648K mutation in HR2 (pathway II) emerged and were In one of these cultures, mutations arose in residues 319 and 306, which are located on antiparallel ␤-hairpin strands in the V3 loop and possibly influence each other in a compensatory manner (65). The two cultures in pathway I were characterized by the E560K mutation in HR1 together with mutations that may affect CD4 interactions, including L125 and E429 (38), and by the Q577R mutation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Several recently described highly potent human MAbs, including PGT128, are also against the C-terminal region of V3, as well as its associ-ated glycans (26). Many of the anti-V3 MAbs are characterized by structural methods, including protein crystallography and the nuclear magnetic resonance (NMR) method (19,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These structural studies of MAbs against the V3 crown showed that they have, in general, two antigen-binding modes.…”
mentioning
confidence: 99%